Retaining talents: unraveling employee retention factors in Moroccan private academic institutions - El Mountasser, Rabab; Sahraoui, Doha (Frontiers in Education, 2025)
This empirical study investigates the factors influencing employee retention in private higher education institutions in Morocco. Utilizing a quantitative approach, we developed and empirically tested an original conceptual framework based on primary data collected from 196 employees in these institutions. The research examines seven key factors affecting employee retention: remuneration and rewards, performance appraisals, organizational climate, supervisor support, training and development, career opportunities, and job satisfaction. The findings provide actionable insights for managers in private academic institutions, emphasizing effective employee retention strategies. Key recommendations include the establishment of career development programs, personalized growth plans, and ongoing skill development initiatives. Organizations are encouraged to conduct comprehensive needs assessments to tailor training programs emphasizing both technical and soft skills. Fostering a positive work environment, offering regular feedback, and addressing job satisfaction are essential to enhancing employee commitment, reducing turnover, and maintaining a competitive edge.